More information, better knowledge? The effects of information campaigns on aid beneficiaries' knowledge of aid projects - Alexander de Juan; Paul Hofman; Carlo Koos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Aid beneficiaries know very little about development interventions in their own communities. This lack of transparency and information is likely to reduce beneficiaries' ability and willingness to become active in local development. It may also dampen intended aid effects on beneficiaries' political and social attitudes. Can targeted information campaigns strengthen beneficiaries' understanding of aid projects? We test the effects of two types of interventions: the provision of information only and the combination of information and feedback opportunities. We embed these interventions in a panel survey in rural Mali. Our information treatment is highly customized to specific local aid projects in respondents' locations and corresponds to beneficiaries' ex-ante information demands. Nonetheless, two months after the campaign, we find only small treatment effects on respondents' project-specific knowledge (type, location) and no effects on their procedural knowledge (selection mechanisms). Only people with favourable ex-ante views of the state's rule adherence and self-identified non-beneficiaries tend to update their views on procedural knowledge. Finally, we find that the combined information and feedback treatment has an effect on respondents' subjective knowledge, which we interpret as promising mechanisms for engaging and identifying with aid projects.
Keywords: D8; D7; 330; development aid; information campaign; fragile states; RCT